Occurrence of the Sylvatic Yellow Fever Vector Mosquito Haemagogus leucocelaenus (Diptera: Culicidae) in an Atlantic Forest Fragment of the Touristic State of Rio de Janeiro, Brazil. Issue 6 (14th October 2022) - Silva, Shayenne Olsson Freitas; de Mello, Cecilia Ferreira; Érico Guimarães, Anthony; José Leite, Paulo; Alencar, Jeronimo
Abstract: The yellow fever virus is estimated to cause 30, 000 deaths each year worldwide, with the majority of cases and deaths occurring in Africa. The virus is also endemic to Central and South America, including northern and western Brazil. The sylvatic cycle of the virus is related to wild and rural areas, with nonhuman primates as the primary host and wild mosquitoes, specifically from the genera Haemagogus, as vectors. The diversity of the mosquito community plays a significant role in the increase of pathogen transmission to humans. In the present study, we detected fluctuation in populations of vector mosquitoes using ovitraps for Culicidae egg collection. The study area is a forest fragment of the Atlantic Forest, one of the most threatened biomes in Brazil. This biome has been suffering significant deforestation due to anthropic activity. Worryingly, the proximity of human populations to forest environments increases the risk of spreading disease from forest fragments to urban areas. Our findings showed that the highest egg abundance occurred in December 2019, with a significant difference ( p = 0.005) between rainy and dry seasons. Most eggs were collected during the rainy period. Subsequent quantification of specimens from epidemiologically relevant species hatched from field-collected eggs resulted in 1, 131 (86%) Haemagogus leucocelaenus (Dyar & Shannon, 1924), 111 (8%) Aedes terrens (Walker, 1856), 47 (4%) Aedes albopictus (Skuse, 1894), and 21 (2%) Haemagogus janthinomys (Dyar, 1921). Finally, we assessed the behavior of different vector species performing oviposition on the same breeding site. The highest correlation coefficient was observed between Ae. albopictus and Ae. terrens (rho = 0.52) concerning other Culicidae species. Therefore, we believe that Culicidae population surveillance is crucial for disease monitoring since the increase in specimens of a number of vector species influences the emergence of yellow fever cases in nonhuman primates and human populations.